An exploration of clinical interventions provided by pharmacists within a complex asthma service - LeMay KS; Saini B; Bosnic-Anticevich S; Smith L; Stewart K; Emmerton L; Burton DL; Krass I; Armour CL (Pharmacy Practice, 2015)
Background: Pharmacists in Australia are accessible health care professionals, and their provision of clinical pharmacy interventions in a range of areas has been proven to improve patient outcomes. Individual clinical pharmacy interventions in the area of asthma management have been very successful. An understanding of the nature of these interventions will inform future pharmacy services. What we do not know is when pharmacists provide a complex asthma service, what elements of that service (interventions) they choose to deliver. Objective: To explore the scope and frequency of asthma-related clinical interventions provided by pharmacists to patients in an evidence-based complex asthma service. Methods: Pharmacists from 4 states/territories of Australia were trained in asthma management. People with asthma had 3 or 4 visits to the pharmacy. Guided by a structured patient file, the pharmacist assessed the patient’s asthma and management and provided interventions where and when considered appropriate, based on their clinical decision making skills. The interventions were recorded in a checklist in the patient file. They were then analysed descriptively and thematically. Results: Pharmacists provided 22,909 clinical pharmacy interventions over the service to 570 patients (398 of whom completed the service). The most frequently delivered interventions were in the themes ‘Education on asthma’, ‘Addressing trigger factors’, ‘Medications – safe and effective use’ and ‘Explore patient perspectives’. The patients had a high and ongoing need for interventions. Pharmacists selected interventions based on their assessment of perceived need then revisited and reinforced these interventions. Conclusion: Pharmacists identified a number of areas in which patients required interventions to assist with their asthma management. Many of these were perceived to require continuing reinforcement over the duration of the service. Pharmacists were able to use their clinical judgement to assess patients and provide clinical pharmacy interventions across a range of asthma management needs.